2022
DOI: 10.1063/5.0080838
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening of tribological properties of monolayer films using molecular dynamics and machine learning

Abstract: Monolayer films have shown promise as a lubricating layer to reduce friction and wear of mechanical devices with separations on the nanoscale. These films have a vast design space with many tunable properties that can affect their tribological effectiveness. For example, terminal group chemistry, film composition, and backbone chemistry can all lead to films with significantly different tribological properties. This design space, however, is very difficult to explore without a combinatorial approach and an aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…To that extent only few studies have shown the potential to explore this data wisely and efficiently in the field of tribology. [315][316][317][318] Table S8 (ESI †) tabulates these four articles describing their tribological investigations on different materials using ML algorithms in MD and DFT.…”
Section: Applications Of ML Integrated With Computational Modeling Te...mentioning
confidence: 99%
See 4 more Smart Citations
“…To that extent only few studies have shown the potential to explore this data wisely and efficiently in the field of tribology. [315][316][317][318] Table S8 (ESI †) tabulates these four articles describing their tribological investigations on different materials using ML algorithms in MD and DFT.…”
Section: Applications Of ML Integrated With Computational Modeling Te...mentioning
confidence: 99%
“…Besides, the RF models trained on a limited dataset could still give meaningful predictions for monolayer designs outside the training set, which suggested a good transferability. 315 Kadupitiya et al conducted NEMD simulations and applied PCA on the data obtained from these simulations. 316 Specifically, a study was conducted to investigate the rheological properties of squalane under elastohydrodynamic lubrication (EHL) conditions, the lubricant under large pressure of more than 500 MPa and strain rate greater than 10 5 s À1 , which is difficult to achieve in an experiment at the same time.…”
Section: Applications Of ML Integrated With Computational Modeling Te...mentioning
confidence: 99%
See 3 more Smart Citations